TRANSFORMASI METODE PEMBELAJARAN PENDIDIKAN AGAMA ISLAM: DARI KONVENSIONAL KE PENDEKATAN STUDENT-CENTERED LEARNING - Fifi Risana; Herlina; A. Ikhsan Muhtar Hadi; Angga Pratama; Fadila Rahmah; Imam Syafe’i (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Student-Centered Learning (SCL) based learning allows students to be more active, independent, and responsible in the learning process. In Islamic education, this model still adheres to cultural values ​​and Islamic teachings to form competent individuals as caliphs on earth. Although the Independent Curriculum has been implemented in various schools, Islamic Religious Education (PAI) teachers still tend to use conventional methods. However, this method is modified by utilizing technology to make learning more effective and interesting. This study also evaluated the application of SCL in PAI subjects. The results of observations showed an increase in student independence in finding learning resources, although some still depended on teachers. In this model, teachers act as facilitators who encourage students to be more active in using technology. Overall, SCL has the potential to improve students' skills and knowledge by placing them at the center of learning, while teachers act as supporters of their development.